From heavy cannabis use to psychosis: is it time to take action?. (27th March 2023) - Johnson-Ferguson, L.; Di Forti, M.
Abstract : Cannabis is one of the most widely used recreational drugs among people with clinical psychosis, after nicotine and alcohol. There has been a debate in psychiatry about whether or not we can infer a cause-and-effect relationship between the use of cannabis and psychotic disorders. In this editorial, we first present and critically discuss the evidence to date of the association between heavy cannabis use and psychosis. We argue that while the biological mechanisms underlying individual susceptibility to develop a psychotic disorder following heavy cannabis use are still unknown, heavy cannabis use remains the most modifiable risk factor for the onset of psychotic disorders and for its clinical and functional outcome. This demands a clear move towards both primary and secondary prevention intervention to reduce the impact of heavy cannabis use on the incidence and prevalence of psychotic disorders.